KONTRIBUSI PELAKSANAAN PENGAWASAN TERHADAP KINERJA PEGAWAI PADA DINAS PENDIDIKAN KOTA SAWAHLUNTO - Nova Amelia (Jurnal Bahana Manajemen Pendidikan, 2014)
This study aims to determine whether the execution of observation by head contribute to officer performance On Duty Education of Town of Sawahlunto . Population of this research is all of employers 45 persons and 40 persons as a sample. The technique used tables of krecje . The tool to collect the data is questioner Likert scale models. Data were analyzed using product moment correlation formula, Test-r, t and t-test to see the contribution of KP. Results of data analysis showed that the performance of the officerr are rather high category (75,6%), execution of observation by head. are less able to the category (69,8%), and there is a contribution to the execution of observation by head performance of officer among 40,96% in 95%. Kata Kunci; Pelaksanaan Pengawasan, Kinerja Pegawai